TEACHING VOCABULARY THROUGH SNAKE AND LADDER BOARD GAME IN THE TENTH GRADE OF SMA MUHAMMADIYAH 1 MALANG - Fitriana, Dita; Maro, Rahmawati Khadijah (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
Vocabulary is the language resource, students have to know vocabularies to produce sentences. Thus, the aim of this study was to find out whether snake and ladder board game could improve students’ vocabulary mastery or not. The subject analyzed in this research were the tenth grade students of SMA Muhammadiyah I. The experimental group was X-IPS-I while the control group was X-IPS-II.This study employed quantitative research design. This design was selected due to this present study was required a concrete evidence whether Snake and Ladder Board Game could enhance students’ vocabulary mastery in senior high school or not. In this study the instruments used were pre-test, treatment, and post-test. The pre-test was given to both experimental and control group. After the pre-test was given to both groups, then the experimental group was treated or taught by using snake and ladder board game, while the control group was not treated by using snake and ladder board game. After that, the post-test was also given to both experimental and control group. The researcher used t-test to know the significant difference between the mean score of the experimental and control group. The process of t-test was counted using computer SPSS 17 version.The result of this study was shown that snake and ladder board game could improve students’ vocabulary mastery due to the score of pre-test in control group was higher than the pre-test score of experimental group. Otherwise, the post-test score of experimental group was higher than the control group. Accordingly, related to the result of this experimental research, the researcher concludes that snake and ladder board game can improve students’ vocabulary mastery in the first year students of senior high school.